Explicações de estudantes do ensino médio sobre o murchar de uma folha de alface temperada: evidências de mudança de teoria-em-uso - Carmen Maria de Caro Martins (2004)
We discuss how high school students use the knowledge they have about osmosis to explain why lettuce leaves shrivel after been salt spiced. Evidences suggest that students can handle their acquired classroom knowledge in order to elaborate the required explanation. We detected that the students use their acquired classroom knowledge and metacognitive ability to improve their explanations, especially towards the epistemological orientation. During a task resolution the students proficiency about osmosis and the metacognitive ability were closely associated to their handled theory- in-use. There are also evidences that both the attention towards the task and the reflexive processes can help to change the theory-in-use.